2011
DOI: 10.1016/j.ijggc.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Combining power plant water needs and carbon dioxide storage using saline formations: Implications for carbon dioxide and water management policies

Abstract: a b s t r a c tResearch involving management of carbon dioxide has increased markedly over the last decade as it relates to concerns over climate change. Capturing and storing carbon dioxide (CO 2 ) in geological formations is one of many proposed methods to manage, and likely reduce, CO 2 emissions from burning fossil fuels in the electricity sector. Saline formations represent a vast storage resource, and the waters they contain could be managed for beneficial use. To address this issue, a methodology was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Bergmo et al 10 examine "passive" brine extraction (i.e., extraction of brine driven only by CO 2 injection and not by active pumping) and conclude that, to utilize more than 1−2% of the pore space for CO 2 storage, it is necessary to produce "massive" amounts of brine from the formation. Kobos et al 11 investigated "active" brine extraction while storing CO 2 from a 1848 MW coal-based power plant and found that approximately 6% of the power plant's cooling water requirements could be met from the extracted and treated saline waters. Birkholzer et al 12 demonstrate use of brine extraction to minimize pressure buildup at specific locations, such as near a fault.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bergmo et al 10 examine "passive" brine extraction (i.e., extraction of brine driven only by CO 2 injection and not by active pumping) and conclude that, to utilize more than 1−2% of the pore space for CO 2 storage, it is necessary to produce "massive" amounts of brine from the formation. Kobos et al 11 investigated "active" brine extraction while storing CO 2 from a 1848 MW coal-based power plant and found that approximately 6% of the power plant's cooling water requirements could be met from the extracted and treated saline waters. Birkholzer et al 12 demonstrate use of brine extraction to minimize pressure buildup at specific locations, such as near a fault.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Systems with the above attributes can be simulated to a degree by representing the agents and the interaction structures, but they are hard to understand analytically 2 . The approach employed in this analysis is conceptually based on our earlier work in agent-based modeling (Darley and Outkin, 2007), energy modelling work (Barter et al, 2012;Kobos et al, 2011), and economic disruption modelling work (Vargas and Ehlen, 2013). As a departure from normative approaches in economics, our agents are boundedly rational and can be data driven.…”
Section: Agent-based Modeling To Represent Ng Agents and Interaction mentioning
confidence: 99%
“…Samples taken at depths shallower than 2,500 ft were not included in this trimmed data set, except where no other data points were available for a specific formation. The 2,500-ft depth limit was selected to eliminate data points at depths that do not meet the pressure requirements for successful carbon sequestration (Kobos et al 2009). …”
Section: Water Quality Data For Geological Formations Likely To Be Usmentioning
confidence: 99%
“…This is illustrated in Figure 10. For these estimates CO 2 density values of 0.65 to 0.78 g/cm 3 were used (Bentham andKirby 2005 andKobos et al 2009). Using these assumptions, 1,300 to 1,500 L of water could be extracted and managed for every metric ton of CO 2 sequestered.…”
Section: Extracted Water Quantity Estimatesmentioning
confidence: 99%